1
$\begingroup$

Let

$$I_n = \int_0^{\pi/2} x^n \cos(2x)dx,\,\,\, n = 0,1,2 \ldots$$

(a) Evaluate $I_0$

(b) By using integration by parts twice, or otherwise, show that a reduction formula for $I_n$ is

$$I_n = -\frac{\pi^{n-1}n}{2^{n+1}} - \frac{n(n-1)}{4} I_{n-2}$$

I have evaluated $I_0=0$. It's (b) I'm having issues with. I've come to the conclusion that I need to integrate by parts $\int_0^{\pi/2} (x\cos(2x))(x^{n-1}\cos(2x))dx$ twice. Is this correct?

Thanks

$\endgroup$
  • 1
    $\begingroup$ You need to integrate by parts twice, the first time the cosine turns to a sine and the second you get the cosine back.... $\endgroup$ – marwalix Apr 11 '15 at 15:35
0
$\begingroup$

Let $$ f(t) = \int_{0}^{\pi/2}e^{tx}\cos(2x)\,dx = -\frac{t}{4+t^2}\left(1+e^{\frac{\pi t}{2}}\right)\tag{1}$$ where the last identity follows from considering $\cos(2x)$ as $\text{Re}(e^{2ix})$.

By differentiating under the integral sign, we have: $$ I_n = \frac{d^n f}{dt^n}(0) \tag{2}$$ from which it follows that: $$ f(t) = -\frac{t}{4+t^2}\left(1+e^{\frac{\pi t}{2}}\right) = \sum_{n\geq 0}\frac{I_n}{n!}\,t^n \tag{3}$$ and since the middle term vanishes for $t=0$, we have $I_0=0$.

Now we can write $(4+t^2)\,f(t)$ in two different ways, namely: $$ -t\left(1+e^{\frac{\pi t}{2}}\right) = -t-\sum_{n\geq 0}\frac{\pi^n}{2^n n!}t^{n+1} \tag{4} $$ and: $$ \sum_{n\geq 0}\frac{I_n}{n!}(4t^n+t^{n+2})\tag{5} $$ and by comparing the coefficients of $[t^n]$ in $(4)$ and $(5)$ our reduction formula follows.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.